(untitled) (ModaPalavra e-periódico, 2009)
This essay aims to present an initial study on the implementation of hypermedia resource to support the presential teaching of the discipline of fashion illustration degree courses in Fashion Design in Santa Catarina. For this, the essay begins by presenting the topic of fashion and illustration of its possibilities of development, with focus on vector drawing programs, as important tool in the implementation of this discipline. Then talks about the distance learning and hypermedia as the main resource used by the Internet and the educational processes can be optimized with the use of these new technologies. Finally, it is suggested that an initial proposal for a site with content of fashion illustration to complement the traditional teaching of this discipline.